Neurotoxic mechanisms and safety assessment of nanomaterials in neurotoxicology - Shi Haonan (MATEC Web of Conferences)
This research examines the neurotoxic effects associated with nanomaterials, focusing on their ability to induce oxidative stress, cause mitochondrial dysfunction, penetrate the blood-brain barrier, disrupt neurotransmitter systems, and generate genotoxic effects. As nanotechnology continues to advance, there are significant improvements in the methods used for characterizing these materials and their applications in fields, such as medicine and environmental remediation. These technological strides, however, highlight the critical need for extensive toxicological studies to better understand the potential hazards posed by nanomaterials. Furthermore, the development and enforcement of stringent regulatory frameworks are essential to manage these risks effectively. Looking forward, research should concentrate on the development of nanomaterials engineered to be inherently safe, utilizing “Safe-by-Design” methodologies. Such strategies are crucial in advancing the design of nanomaterials that minimize potential risks while maximizing their beneficial uses. Strengthening regulatory guidelines is also imperative to ensure that the integration of nanomaterials into new applications proceeds safely. Integrating comprehensive safety assessments with the innovative deployment of nanomaterials promises to maximize their benefits while safeguarding public health and the environment.